2019
DOI: 10.1186/s12879-019-4676-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of AIDS and non-AIDS related mortality among people living with HIV in Shiraz, southern Iran: a 20-year retrospective follow-up study

Abstract: BackgroundHuman Immunodeficiency Virus (HIV) infection has become a global concern. Determining the factors leading to death among HIV patients helps controlling Acquired Immune Deficiency Syndrome (AIDS) epidemic. Up to now, little is known about mortality and its determinants among people living with HIV in the Middle East and North Africa (MENA) region, including Iran. The purpose of this study was to assess the risk factors of AIDS-Related Mortality (ARM) and Non-AIDS-Related Mortality (NARM) among people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
4
25
0
3
Order By: Relevance
“…Consistent with different studies conducted in different countries, 14,22,28,29 in this study, we found that patients with advanced last known WHO stage (stage III/IV) had higher hazards of death as compared with those whose last known WHO stage was I/II. This might be because infections are the leading causes of death, notably opportunistic infections such as tuberculosis is the main causes of death in HIV patients.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with different studies conducted in different countries, 14,22,28,29 in this study, we found that patients with advanced last known WHO stage (stage III/IV) had higher hazards of death as compared with those whose last known WHO stage was I/II. This might be because infections are the leading causes of death, notably opportunistic infections such as tuberculosis is the main causes of death in HIV patients.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, it should be noted that AIDS‐ and non‐AIDS‐related mortality rates using data from this 20‐year cohort study have been presented previously [61].…”
Section: Discussionmentioning
confidence: 99%
“…Sub-Saharan Africa, worst affected region, in particular accounts for 71% of HIV infections [1]. Life expectancy for patients infected with HIV has improved significantly in the era of highly active antiretroviral therapy (HAART) [2]. e decline in hospitalization due to HAART, however, has been unevenly distributed and inconsistent.…”
Section: Introductionmentioning
confidence: 99%